Description of Ictal HFO Mapping in Patients with Both Temporal and Extratemporal Seizure Focus - Juan G. Ochoa; Walter G. Rusyniak (Neurology Research International)
Objective. Review presurgical use of ictal HFO mapping to detect ictal activation areas with dual seizure focus in both the temporal and extratemporal cortex. Methods. Review of consecutive patients admitted to the University of South Alabama Epilepsy Monitoring Unit (SouthCEP) between January 2014 and October 2015, with suspected temporal lobe epilepsy and intracranial electrode recording. Ictal HFO localization was displayed in 3D reconstructed brain images using the patient’s own coregistered magnetic resonance imaging (MRI) and computed tomography (CT) with the implanted electrodes. Results. Four of fifteen patients showed evidence of extratemporal involvement at the onset of the clinical seizures. Ictal HFO mapping involving both frontal and temporal lobe changed the surgical resection areas in three patients where the initial surgical plan included only the temporal lobe. Resection of the ictal HFO at the onset of the seizure and the initial propagation region was associated with seizure freedom in all patients; follow-up period ranged from 12 to 25 months. Significance. Extratemporal ictal involvement may not have clinical manifestations and may account for surgical failure in temporal lobe epilepsy. Ictal HFO mapping is useful to define the ictal cortical network and may help detect an extratemporal focus.